THE SUPERIORITY IN VERONICA ROTH’S DIVERGENT - Angel Lineleyan; Agustine C. Mamentu; Delli Sabudu (Program Studi Pendidikan Bahasa Inggris, 2022)
Superiority is being superior, this attitude can be seen in the character of Beatrice prior, the main character in Divergent novel. Because of this attitude, Beatrice played an important role in saving the Abnigation from massacre. Being superior means suppressing feelings of inferiority to be more cnfident in doing social things and making choices in life This research has a purpose to analyze the superiority of Tris in Veronica Roth’s Divergent. This study categorized as qualitative research design because the data collection was in the form of words rather than numbers. In analyzing the data the writer used objective approach, this approach focused only at the interrelationship between internal elements of the novel they are character and characterization, theme, plot and setting. Research finding shows that Tris has a quality of superior because she has the whole ability or skills of five faction and it caused some of superior quality they are Being Better to be Brave, Powerfull make Her Hero, Greater and Skillful make Her equal to man